In-Vitro Comparison of Mechanical and Physical Properties of Various Provisional Restoration Materials - Burduroğlu, Hatice Defne; BURDUROĞLU, HATİCE DEFNE (My University, 2019)
IN-VITRO COMPARISON OF MECHANICAL AND PHYSICALPROPERTIES OF VARIOUS PROVISIONAL RESTORATION MATERIALSBurduroglu, Defne *, Keyf, FilizBezmialem Vakif University, Faculty of DentistryDepartment of ProsthodonticsIstanbul, TurkeyKeywords: provisional restoration, color stability, flexural strengthPurpose/Aim: It is important for patient comfort and satisfaction that provisional restorations should not fracture, get deformed andshow discoloration while in use. In our study, 6 different provisional restoration materials were subjected to micro hardness test andflexural test in order to measure mechanical strength, surface roughness test and discoloration tests in order to evaluate esthetics. Withthe help of these tests, we searched for materials that are advantageous during clinic use.Materials and Methods: Vita CAD-Temp and Ivoclar Telio-CAD blocks for CAD/CAM are used in our study. Other materials used inour study are Revotek LC (UDMA), Protemp 4 (Bis-acryl), Dentalon Plus (PEMA) and Imident (PMMA). Samples for 3-point bendingtest are manufactured with dimensions 2 x 2 x 25 mm according to ISO 4049 (n=15). Samples were loaded with a universal testingmachine until fracture occurred. For micro hardness, surface roughness and discoloration tests, disc shaped samples with 10 mmdiameter and 2 mm thickness were manufactured (n=15). Baseline color measurements were made after Vickers micro hardness andsurface roughness tests. As a coloring agent, coffee was chosen. All samples were immersed in coffee solution for 7 days. Second colormeasurements were made. ?E values, which shows discoloration, were calculated. Statistical analysis of the data was made with SPSSfor Windows 11.5. Kruskal Wallis test was used in order to evaluate level of significance (p<0,05).Results: Flexural strength values varied between 146 MPa and 63 MPa. The strongest groups were Imident and Protemp 4. Microhardness and surface roughness evaluation showed methacrylate resins are better than other groups. As color stability, PMMA groupswere found to discolor less than other groups. Revotek LC and Protemp 4 showed clinically unacceptable ?E values (?E>3.3).Conclusions: Based on this study data, it is advised to use heat polymerized PMMA when long-term use is indicated.
Keywords: Burduroğlu H. D. , -In-Vitro Comparison of Mechanical and Physical Properties of Various Provisional Restoration Materials-, ICP & EPA JOINT MEETING, Amsterdam, Hollanda, 4 - 07 Eylül 2019, ss.145